Clinical risk factors for venous thromboembolus in users of the combined oral contraceptive pill - Black, Corri (Blackwell Science Inc, 2002)
AIMS: To estimate the risk of venous thromboembolism among women prescribed the oral contraceptive pill who have acute clinical conditions such as lower limb fractures, compared with women with idiopathic venous thromboembolism. METHODS: A nested case-control analysis using the General Practice Research Database, January 1993 to December 1999 was carried out. The participants were women aged 15–39 years, prescribed third generation oral contraceptives (gestodene and desogestrel) or oral contraceptives containing levonorgestrel. The main outcome measures were odds ratios as a measure of the relative risk estimate for venous thromboembolism in women with clinical conditions that predispose to VTE. RESULTS: The adjusted relative risk estimate for venous thromboembolism among patients with the acute clinical conditions, compared with those without such illness, and adjusted for oral contraceptive use, was 17 (95% CI 6.5, 46). CONCLUSIONS: This paper documents the strong independent association between certain acute clinical conditions and venous thromboembolism in women prescribed oral contraceptives. Failure to accurately identify and exclude such patients from a study of the effect of oral contraceptives on the risk of venous thromboembolism would result in an underestimate of the risk of venous thromboembolism associated with oral contraceptives.